Pendampingan Pemakmuran Masjid Kampung Dalam Mewujudkan Kehidupan Masyarakat Yang Religius, Ideal Dan Harmonis Di Dusun Paleran, Desa Gunung Malang, Kecamatan Sumberjambe, Kabupaten Jember - Hasbi Ash Shiddiqi (BADAN PENERBIT STIEPARI PRESS, 2021)
Since the time of the Prophet Muhammad, mosques have been the center of Muslim activities. Even though the meaning of the word is that a mosque is a place of prostration to Allah SWT, history shows that mosques are not only used for ritual activities. In the long course of Islamic history, it can be said that mosques also played a significant role in the development of Islamic civilization. Therefore, in rebuilding Islamic civilization, which is able to spread grace to the surrounding environment, it is basically a center for Muslim activities. The mosque is located in a remote village, on a mountain slope far from the crowds. The majority of the population are advanced farmers who earn good incomes. Even though the average citizen has low education, most of them are Islamic boarding school alumni with strong religious basics. The population in this hamlet is dominated by adults and the elderly. Assistance through Community Development using the PAR (Participatory Action Research) method and theoretical concepts, is expected to be able to provide contributions, benefits and changes that are expected to occur in terms of the prosperity of the mosque and the realization of a religious, ideal and harmonious community life. companions include: First, the existence of new mosque takmir management. This is related to the management of the management structure and the congregational prayer imam's schedule. Second, changes in residents' awareness of the existence of flowing water sources that can be utilized and managed together in a cooperative manner. Third, changes in the attitudes of young people in Paleran hamlet towards self-confidence for a more advanced life. This is characterized by their more active role in every activity. It is no longer awkward and reluctant to get involved directly in helping, even though you are still not able to be independent (still based on instructions). Fourth, change towards social change that upholds solidarity (togetherness) between residents to build a proper ablution place in the mosque where they worship.